Agricultural Drones : a Peaceful Pursuit - Krishna, K. R. (Boca Raton, FL : CRC Press, 2017)
"Agricultural Drones: A Peaceful Pursuit deals with the increasing importance of the role of aerial robots in managing agricultural farms and natural resources. Agricultural drones are expected to revolutionize the way we conduct agronomic procedures and maintain natural vegetation on earth. This new book provides a wealth of information on drone usage in agriculture. The book explores the advanced sensors and imaging capabilities of drones that give farmers new ways to increase yields and reduce crop damage. An introductory chapter provides historical data, with details about various models of drones as well as the most recent and popular agricultural drones in usage. The book goes onto discuss such topics as the use of drones for soil fertility, production agronomy, irrigation, weed control, pest and disease control, grain yield forecasting, and economic advantages from drone use. This timely and useful volume will be a valuable resource for faculty, agricultural extension officers, and farmers and farm consultancy agencies. This book would also serve as an excellent textbook for students in agriculture, engineering, and geography."--Provided by publisher.
Chapter 1 Drones in Agriculture / K. R. Krishna -- chapter 2 Drones to Study Natural Resources and Vegetation / K. R. Krishna -- chapter 3 Drones in Soil Fertility Management / K. R. Krishna -- chapter 4 Drones in Production Agronomy / K. R. Krishna -- chapter 5 Drones in Irrigation and Water Management During Crop Production / K. R. Krishna -- chapter 6 Drones to manage weeds in crop fields / K. R. Krishna -- chapter 7 Drones in crop disease and pest control / K. R. Krishna -- chapter 8 Drones in crop yield estimation and forecasting / K. R. Krishna -- chapter 9 Economic and regulatory aspects of agricultural drones / K. R. Krishna -- chapter 10 Drones in agriculture: summary and future course / K. R. Krishna.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY & ENGINEERING -- Agriculture -- General; TECHNOLOGY & ENGINEERING -- Environmental -- General; Aeronautics in agriculture; Drone aircraft; Agricultural innovations